Computational Elucidation Of Binding Interactions For Thicapa And Poet On Amyloid Beta 42 And Presenilin 1 In Treating Alzheimer’s Disease - Mohd Suhaimi, Ahmad Marwazi (2024)
AD begins with memory and cognitive impairment and progresses to speech and movement skills which affects 35% of 80-year-olds adult. According to the amyloid cascade hypothesis, two proteins which are Amyloid Precursor Protein (APP), and Presenilin 1 (PS1) play a vital role in contributing to AD. Mutated APP and PS1 are shown to be responsible for the production of pathogenic amyloid-beta (Aβ42) peptide in AD patient, which then forms Aβ42 plaques and deposited in the brain. Presenilin 1 (PS1) is the primary component of γ-secretase which catalyses the cleavage of APP (neuron development) especially at the beta region of APP in both amyloid pathways.